Hubungan Agama dan Negara Menurut Perspektif Nicolaus Driyarkara - Ngoranmele, Fenansus (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2020)
Today the issue of the relationship between religion and the state is very relevant to the concrete situation in Indonesia. The polemic shows the difference marked by the phenomenon of pluralism on the one hand and the trap of privatization and the politicization of religion on the other. In this case, Driyarkara offers a paradigm of differentiation and an overreach of identity politics to pay attention to the relationship between religion and the state. Apart from that, he is questioning the extent to which the paradigm of differentiation and excess of identity politics is able to support the phenomenon of pluralization of modern society. Religion and the state need to be differentiated as two different works. However, the distinction between religion and state does not aim to displace religion into the private sphere, but rather embrace religion to be able to participate in public space and state life by playing a role as a source of public morality or civil religion.